Intermittent hypoxic tranining at low altitude and impact on EPO and VEGF - Mikulski, T.; Ziemba, A. (Medicina Sportiva, 2013)
Intermittent hypoxic training (IHT) is a no-invasive, no-pharmacological method enhancing performance, using the adaptive changes to decreased oxygen content in air. Erythropoetin (EPO) and vascular epithelium growth factor (VEGF) are very important factors in endurance sports, enhancing oxygen transport capacity and delivery to the working muscles. Aim of the study was to evaluate, if altitude training stimulates synthesis of both EPO and VEGF, which among many other factors are products of expression of hypoxia inducible factor (HIF). Methods: Intermittent hypoxic training was performed in 12 runners of national track and field team (age 25±1 yrs, BMI 19.8±0.5 kg/m2) using a four person hypoxicator delivered by Go2Altitude (Australia). Each IHT session took approximately one hour and consisted of subsequent periods of breathing with hypoxic and room air. The length of those intervals is essential in IHT and is determined with hypoxia tolerance test performed before the first IHT session. According to the results of hypoxia tolerance test the time of breathing hypoxic air was determined ranging from 3 to 8 minutes with rest intervals of breathing room air of 2 to 4 minutes. Number of intervals creating the single IHT session was set so that each subject in total breaths hypoxic air for 35 to 40 minutes; the total hypoxic dose was the same in all subjects. In first three IHT sessions the air of 14% oxygen concentration was used (usually corresponding to saturation of 85%) and in consecutive days it was gradually lowered to the value resulting in oxygen saturation in subjects` blood of 78-80%. The minimum oxygen concentration used was 11.5% what represents the altitude of approx. 4800 meters above sea level. Blood samples for determination of EPO and VEGF concentrations were obtained from antecubital vein in the morning in the fasting state before, in 5th and 14th day of IHT. Concentrations of EPO and VEGF were determined using the ELISA tests. Results: Blood concentration of EPO increased significantly after 4 days of IHT (from 6.7±1.2mlU/ml to 11.7±0.9 mlU/ml, P<0.001) and remained elevated till the end of IHT (9.8±0.9mlU/ml).Also VEGF levels responded to IHT demonstrating the significant increase from 22.5±6.0 pg/ml to 366.0±49.2 pg/ml, P<0.001. Conclusion: Altitude training at sea level with IHT method was well tolerated by all athletes and showed positive impct on molecular level on some important factors involved in exercise metabolism. Thus, IHT can be considered as a recommended option to be combined with classic altitude training.